2022
DOI: 10.1186/s13063-021-05950-x
|View full text |Cite
|
Sign up to set email alerts
|

Fasting before living-kidney donation: effect on donor well-being and postoperative recovery: study protocol of a multicenter randomized controlled trial

Abstract: Background One of the main effectors on the quality of life of living-kidney donors is postoperative fatigue. Caloric restriction (CR) and short-term fasting (STF) are associated with improved fitness and increased resistance to acute stress. CR/STF increases the expression of cytoprotective genes, increases immunomodulation via increased anti-inflammatory cytokine production, and decreases the expression of pro-inflammatory markers. As such, nutritional preconditioning by CR or STF represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…This was not as expected, given that on average, women tend to crave sweet treats more than men 37 38. Lastly, study personnel were found to significantly rate lower, influenced by their involvement in the active trials,29–31 possibly setting higher standards for the coordinating investigator or they were just sad to see a familiar batch of brownies distributed to others. The consistent findings in the subscores support the absence of the ‘Brownie-Effect’.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This was not as expected, given that on average, women tend to crave sweet treats more than men 37 38. Lastly, study personnel were found to significantly rate lower, influenced by their involvement in the active trials,29–31 possibly setting higher standards for the coordinating investigator or they were just sad to see a familiar batch of brownies distributed to others. The consistent findings in the subscores support the absence of the ‘Brownie-Effect’.…”
Section: Discussionmentioning
confidence: 89%
“…We selected 200 email addresses of healthcare professionals from departments associated with the active clinical trials 29–31. The survey was sent twice, on 26 April 2023 and 10 May 2023, and people were given a response window of 6 weeks from 26 April 2023.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest three main pathomechanisms for symptom reduction in OA through fasting. One is the anti-inflammatory effect of fasting that has been shown in animal and human studies (5,13,34,55). This is probably mediated by cellular stress-response mechanisms such as autophagy, mitophagy and sirtuine-activation, as well as systemic hormonal and metabolic responses to nutrient deprivation (5,56).…”
Section: Discussionmentioning
confidence: 99%